1978
DOI: 10.1001/archderm.114.11.1698
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric bowen's disease of the genitalia: spontaneous regression of lesions

Abstract: The phenomenon of multiple lesions of Bowen's disease appearing on the genitalia of young adults is becoming increasingly recognized. We have seen two patients who had genital lesions with histologic features of squamous carcinoma in situ, but with an entirely different clinical appearance. In both patients, varying degrees of spontaneous regression occurred. A conservative approach to management of these lesions is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…10 Several groups then noticed that a proportion of lesions that were morphologically identical to CIS demonstrated spontaneous regression, particularly in young, pregnant patients with multicentric disease. 5,11,12 In order to distinguish these lesions from those which progressed to invasive carcinoma, Wade, Kopf and Ackerman in 1979 coined the term ‘Bowenoid papulosis’. 13 …”
Section: Evolution Of Nomenclature and Current Classificationmentioning
confidence: 99%
“…10 Several groups then noticed that a proportion of lesions that were morphologically identical to CIS demonstrated spontaneous regression, particularly in young, pregnant patients with multicentric disease. 5,11,12 In order to distinguish these lesions from those which progressed to invasive carcinoma, Wade, Kopf and Ackerman in 1979 coined the term ‘Bowenoid papulosis’. 13 …”
Section: Evolution Of Nomenclature and Current Classificationmentioning
confidence: 99%
“…Eisen et al (18) found three cases in the literature of spontaneous regression of bowenoid papulosis in males and also added one case of their own. Resolution of multiple lesions after cryotherapy or biopsy of one lesion has also been described (4,14,18). Our patient had tissue taken from two lesions, and a third lesion was lightly frozen with liquid nitrogen.…”
Section: Discussionmentioning
confidence: 87%
“…The majority of patients who are treated have no recurrences, but there has not been sufficient follow-up to determine long-term recurrence rates. Many cases of spontaneous regression of bowenoid papulosis have been reported, most of these in females in association with pregnancy or delivery (13)(14)(15)18). Eisen et al (18) found three cases in the literature of spontaneous regression of bowenoid papulosis in males and also added one case of their own.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] More recently, a sudden onset of hair loss was observed in 12 patients with infectious mononucleosis due to Epstein-Barr virus. 5 A search of the 6256 individuals in the AA registry in August 2007 revealed that 1586 AA patients were prompted by an environmental factor, infectious mononucleosis, which although self-reported, occurred within 1 week to 6 months before the onset of AA. Vaccination, especially hepatitis B vaccine, is another trigger of AA.…”
Section: Alopecia Areata Triggered or Exacerbated By Swine Flu Virus mentioning
confidence: 99%
“…Although a linear arrangement of lesions in this disorder has been reported, they are relatively rare. [2][3][4][5] The linear arrangement is thought to be formed by the coalescence of papules. To the best of our knowledge, all the reported cases of linear BP have presented with papules around the linear lesions.…”
mentioning
confidence: 99%